EVALUASI PENGGUNAAN OBAT PADA PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS : NARATIVE LITERATURE RIVIEW - Irawan, Wira; Sukandar, Elin Yulinah (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Chronic kidney failure is a condition characterised by a gradual deterioration of renal function over months to years, resulting in the replacement of normal cells by fibrous tissue, impairing the kidneys' ability to effectively filter waste products from the bloodstream. This review article is to examine medications that demonstrate effective therapeutic outcomes in accordance with treatment guidelines for patients with chronic renal failure, based on the criteria of appropriate patient, appropriate drug, appropriate indication, and appropriate dosage. The employed methodology is a narrative literature review, encompassing an examination of 14 papers published between 2015 and 2025. Literature searches were performed using the Google Scholar, PubMed, and Science Direct databases. The search employs the terms